THE IMPACT OF MIND MAPPING TECHNIQUES ON PRE-WRITING ACTIVITIES IN EFL CLASSROOMS - Ratih Laily Nurjannah; Budiati Budiati; Peni Sri Rejeki (TELL - US JOURNAL, 2025)
Mind mapping is believed to be an effective technique for the pre-writing stage. This study aims to investigate the impact of mind mapping technique as a pre-writing activity in EFL classes. This study used a quasi-experimental research design with pre- and post-test control group design. The respondents were seventh grade students of SMPIP Assalamah Ungaran who were divided into two groups: the experimental group, which was given instructions on how to use mind mapping as a pre-writing approach, and the control group was given conventional teaching. A pre-test and post-test on writing performance were given to both groups, and the data collected from these assessments were evaluated and analyzed by comparing the results of the pre-test and post-test assessments. The results showed that there was a significant increase in the mean score of the experimental group by 13.35, while that of the control group by 5.36. This shows that pre-writing activities with mind mapping can improve students' writing skills. The mind mapping technique improves students' writing skills; ideas are more organized, sentences are more complex, the number of sentences is more in accordance with the number of ideas in each of the branches arranged in the mind map, and the relationship between sentences looks better and there is cohesion and coherence between sentences.